Comparison of Head and Neck Cancer Distribution in Turkish and Syrian Populations - Gozde SERİNDERE; Behiye BOLGUL; Didar GURSOY; Sibel HAKVERDİ; Nazan SAVAS (Tehran University of Medical Sciences, 2019)
Background: Although oral health improves in several countries, global problems are still present. Predictably, the disadvantaged and poor population groups in both developing and developed countries have high rate of malign disease. The aim of this study was to evaluate the prevalence of head and neck cancers (HNCs) and to compare them between Syrian and Turkish population. Methods: A total of 4570 patients confirmed to have HNC histopathologically from Hatay Mustafa Kemal University Hospital Pathology report archive were retrospectively evaluated. Among them, 452 were Syrian patients while 4118 were Turkish patients. Data were collected from 2010 to 2017. Gender and age information were taken from medical records. According to the pathological results, HNCs were classified. Results: In 474 patients, HNCs were inscriptived, of which 317 were in males and 157 in females aged 23-80 years with histologically approved cancer of head and neck area. Overall, 100 were Syrian patients while 374 were Turkish patients. In both Syrian and Turkish patients, the most observed HNC was squamous cell carcinoma (SCC). Conclusion: Nowadays, the prevalence of cancer is higher because of the excessive consumption of alcohol, tobacco, chewing, and smoking. For the higher cancer incidence in Syrian refugees, we thought that the impact of war such as stress may have been effective as well as the known several etiologic factors of cancer. For the increased risk of cancer, the early diagnosis of this become more important.